Bundesbank online pilot survey on consumer expectations - Elisabeth Beckmann; Tobias Schmidt (Deutsche Bundesbank, 2020)
The Bundesbank commissioned an online pilot survey on consumer expectations in 2019. This paper presents the methodology of the survey and evaluates its design. The survey proved to be a distinct asset in providing timely data on household expectations at a high frequency, allowing for flexible implementation of randomised controlled trials and analyses based on the panel dimension. One drawback of the survey is that there is likely a selection bias as the survey was conducted online and may not adequately represent the expectations of the offline population. This selection bias cannot be fully offset by recruiting respondents offline.
Keywords: 330; online surveys; household expectations; survey methodology